Rotenone-treated in the Early Life Stages of Zebrafish (Danio rerio) as a Model for Parkinson-like Motor and Non-motor Symptoms and Anxiety-like Behaviour - , André Lucas Corrêa de Andrade; , Renatta Priscilla Ferreira Silva; , Priscila Rafaela Leão Soares; , Thamiris Pinheiro Santos; , Renata Meireles Oliveira Padilha; , Paulo Eduardo da Silva Bastos; , Pabyton Gonçalves Cadena (Archives of Current Research International, 2025)
Background: Rotenone is a pesticide derived from a natural toxin present in plants and is used in agriculture and aquaculture to eliminate unwanted fish. The toxicity of rotenone in fish makes it difficult to determine an optimal dose that efficiently reduces dopaminergic neurons with low mortality. Aims: To establish a zebrafish (Danio rerio) model for Parkinson-like symptoms by evaluating the developmental, teratogenic, and behavioural effects of rotenone, with a specific focus on non-motor and anxiety-like behaviours. Study Design: An in vivo experimental study evaluating dose-response effects of rotenone on zebrafish embryo-larvae. Methodology: The study was conducted at Laboratório de Ecofisiologia e Comportamento Animal (LECA), Universidade Federal Rural de Pernambuco (UFRPE), Recife, PE, Brazil, between August 2020 and July 2021. Zebrafish embryo-larvae were exposed to rotenone (5, 10, 15, and 20 µg/L) from 2 hours post-fertilisation (hpf). Developmental endpoints (epiboly rate, teratogenicity, mortality, morphometry) and behavioural endpoints (thigmotaxis, touch sensitivity, optomotor response) were analysed up to 144 hpf. Results: Rotenone exposure increased mortality and teratogenicity in a dose-dependent manner, yielding an LC₅₀ of 13.88 µg/L and an EC₅₀ of 11.24 µg/L at 96 hpf. Significant reductions in head and body length were observed at all concentrations (P < .05), with a notable decrease of 6% in head length and 5% in body length even at the lowest dose (5 µg/L). Anxiety-like behaviour, indicated by a significant loss of thigmotaxis, was evident at 15 µg/L (P = .013) and 20 µg/L (P = .001), where the response rate dropped from 92% in controls to 68% and 63%, respectively. In contrast, touch sensitivity was only affected at the highest concentration (20 µg/L, P = .009), with the escape response rate dropping from 100% in controls to 85%. The optomotor response was unaffected. Conclusion: Rotenone exposure in early-stage zebrafish effectively models key features of Parkinson's disease, including developmental defects and non-motor symptoms like anxiety-like behaviour. The 10-15 µg/L concentration range offers an optimal window for inducing these phenotypes, establishing a robust and high-throughput model for screening potential therapeutics.